A Call for Urgent Monitoring of Food and Water Security Based on Relevant Indicators for the Arctic - Nilsson, Lena Maria; Destouni, Georgia; Berner, James; Dudarev, Alexy A.; Mulvad, Gert; Odland, Jon Øyvind; Parkinson, Alan; Tikhonov, Constantine; Rautio, Arja; Evengård, Birgitta (AMBIO, 2013)
This perspective paper argues for an urgent need to monitor a set of 12 concrete, measurable indicators of food and water security in the Arctic over time. Such a quantitative indicator approach may be viewed as representing a reductionist rather than a holistic perspective, but is nevertheless necessary for actually knowing what reality aspects to monitor in order to accurately understand, quantify, and be able to project critical changes to food and water security of both indigenous and non-indigenous people in the Arctic. More relevant indicators may be developed in the future, taking us further toward reconciliation between reductionist and holistic approaches to change assessment and understanding. However, the potential of such further development to improved holistic change assessment is not an argument not to urgently start to monitor and quantify the changes in food and water security indicators that are immediately available and adequate for the Arctic context.